2013
DOI: 10.1186/1752-153x-7-51
|View full text |Cite
|
Sign up to set email alerts
|

A critical study on efficiency of different materials for fluoride removal from aqueous media

Abstract: Fluoride is a persistent and non-biodegradable pollutant that accumulates in soil, plants, wildlife and in human beings. Therefore, knowledge of its removal, using best technique with optimum efficiency is needed. The present survey highlights on efficacy of different materials for the removal of fluoride from water. The most important results of extensive studies on various key factors (pH, agitation time, initial fluoride concentration, temperature, particle size, surface area, presence and nature of counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 119 publications
0
35
0
1
Order By: Relevance
“…It is indicated that iron is superior to other adsorbents for removal of F À (Qiao et al 2014) and a mixture of metallic oxides enhances F À adsorption (Tomar and Kumar 2013). The results revealed that iron ore contains relatively high iron and silicon oxides.…”
Section: Characterization Of the Adsorbentmentioning
confidence: 72%
See 1 more Smart Citation
“…It is indicated that iron is superior to other adsorbents for removal of F À (Qiao et al 2014) and a mixture of metallic oxides enhances F À adsorption (Tomar and Kumar 2013). The results revealed that iron ore contains relatively high iron and silicon oxides.…”
Section: Characterization Of the Adsorbentmentioning
confidence: 72%
“…In recent years, scientists suggested composite metal oxide as effective adsorbent for fluoride removal (Tchomgui-Kamga et al 2010a;Sun et al 2011;Tomar and Kumar 2013) and the U.S. Patent Trademark Office approved such novel approaches (Yang et al 2010). Iron ore is a mixture of different metal oxides responsible for the removal of fluoride and is one of the most abundant and cheap materials available anywhere in the Rift Valley.…”
Section: Introductionmentioning
confidence: 99%
“…The control of chemical and physical oxygen functional groups considerably affects their performance on the adsorption process [47]. However, the use of Extended X-ray Absorption Fine Structure (EXAFS), Fourier transform infrared spectroscopy (FTIR), and X-ray absorption near edge structure (XANES) has been employed for the removal of fluoride [48] and arsenic [49] to further study the adsorption mechanism and involvement of functional groups in different adsorbents. These have revealed the involvement of functional groups like hydroxyl and carbonates in the surface, which participate in the adsorption.…”
Section: Adsorption Methods For Arsenic and Fluoride Removalmentioning
confidence: 99%
“…It exists as a diatomic molecule with remarkably low dissociation energy (38 kcal/mol). Fluoride is a persistent and non-biodegradable pollutant that accumulates in soil, plants, wildlife and human beings (Tomar and Kumar 2013). In soil fluoride presents as earth crust (0.6-0.9 %) commonly associated with volcanic activity and gases.…”
Section: Introductionmentioning
confidence: 99%